Analysis Of Consumer Behavior In Buying Interest In Craft Products MSME - Arif, Arif; Asyiah, Ai Kusmiati; Ghonisyah, Ghaling Achmad Abdul (Almana : Jurnal Manajemen dan Bisnis, 2024)
Increased competition in the craft industry and reduced activity in the surrounding community have caused a significant decline in the number of MSMEs, which is indicated by internal and external factors. Rajapolah crafts are increasingly popular with consumers because they prefer modern products compared to crafts made in Rajapolah. Wicker is considered old-fashioned and out of date, especially by the millennial generation. This research aims to analyze how price and product quality influence consumer buying interest in Rajapolah craft products. This research can be expanded as quantitative research with a sample size of 100 respondents. Based on the results that have been carried out, price and product quality have a significant effect on buying interest in Rajapolah handicraft MSME products. It can be concluded that producers, in increasing purchasing interest, need to look at the price and quality aspects of their products.